Development of Project-Based Learning Science Module to Improve Critical Thinking Skills of Junior High School Students - Widodo Setiyo Wibowo; Ekosari Roektiningroem; Norma Bastian; Karina Syahrul Hudda (Universitas Negeri Yogyakarta, 2018)
The study was conducted to develop science module based on project-based learning that is feasible to be implemented in science learning and has potency to build critical thinking skills of junior high school students. The study was Research and Development (RnD), modified from Borg and Gall steps covering only research and information collecting, planning, preliminary form of product development, expert judgment, product revision, and final product. The subjects were 2 expert lecturers (content expert and media expert) and 2 science teachers of SMP N 1 Wonosari. The types of data were quantitative and qualitative. Data were collected by means of SSP validation sheets and disaster preparedness identification sheets. The techniques of data analysis were descriptive analysis of qualitative and quantitative to 5 grading scale. The result of the study shows that science module is feasible to be implemented in science learning and has potency to build critical thinking skills of junior high school students.